ANALISIS TERMOPLASTIK ELASTOMER DENGAN FILLER SERBUK BAN BEKAS - Bunga Fisikanta Bukit; Eva Marlina Ginting; Nurdin Bukit; Fika Yulida (Universitas Quality, 2018)
This study were to find out the mechanical properties (tensile strength, elongation break, and elastic modulus) and morphology of the polyethylene and SIR-20 blends by using a used tire filler. The method used by adding a used tire powder (80 mesh) as a filler on a mixture of recycled SIR-20 and polyethylene (PE) rubber. The composite preparation was carried out by mixing (PE) and SIR-20 rubber as a matrix, polyethylene malaeic anhydride (PEMA) as a compatibilizer, and Sulfur as cross link agent by adding filler (0, 10, 20, 30) phr, in Internal Labopastomil with temperature 1800C and rate of 60 rpm for 14 minutes. The results showed that the mechanical properties decreased with the rise of used tire powder, while the morphological result of the homogeneous mixture.